Factors that effect performance of futures CPO in Malaysia / Mohd Haikal Abdull Raffor - Abdull Raffor, Mohd Haikal (2007)
This paper is done in order to ascertain the effects of the determinants for the performance of the Crude Palm Oil (CPO) namely the price, demand and supply of CPO and the annual interest rates set by the Bank Negara Malaysia against the performance of the Crude Palm Oil Futures (FCPO) traded on the Bursa Malaysia Derivatives Berhad's Futures Exchange. The observation of this research is 11 years which the data collected from 1996 to 2006 annually from Data Stream and internet sources. The methodology for the research used is the Pearson Correlation and Multiple Regression Analysis. The results indicate that there is a significant relationship between the performances of the FCPO with all independent variables namely the price of CPO, supply of CPO, demand of CPO and the interest rates. Besides that, from the view of independent variables individually, all of the independent mentioned above has insignificant relationship with performance of FCPO. From the results of the study, some feasible recommendations are provided for the review of interested parties in order to enhance the predictive power of the movements of the FCPO prices traded on the Bursa Malaysia Derivatives Berhad's Futures Exchange.